Depression and Anxiety Among Pregnant and Non-Pregnant Women During the COVID-19 Pandemic in Isfahan: A Case-Control Study - Khalili Borujeni, Tahereh; Bagheri, Elaheh; Motamedi, Narges; Rajabi, Fatemeh; Movahedi, Minoo; Hajhashemi, Maryam; Haghollahi, fedyeh (Shahroud Journal of Medical Sciences, 2026)
Background: Exploring how the COVID-19 pandemic has influenced depression and anxiety in pregnant and non-pregnant women is essential for informing mental health policies and interventions. This study focuses on measuring these conditions among women in Isfahan City. Methods: The case-control study included 358 participants comprising 179 pregnant women and 179 non-pregnant women referred to the clinics at Shahid Beheshti and Al-Zahra Hospital, Isfahan, during the COVID-19 pandemic from April 2021 to 2022. Beck Depression Inventory (BDI) and the Hospital Anxiety and Depression Scale (HADS) questionnaire were utilized for assessing depression and anxiety. The data obtained was analyzed using the Chi-square test, one-way analysis of variance, and logistic regression analysis. Regression analysis was applied to explore the depression and anxiety-related factors. All statistical analyses were performed using a 5% error and were done via SPSS for Windows version 23 (SPSS Inc., Chicago, IL, USA). Results: The prevalence rate in pregnant women reached 63.7% and 61.9%, against 35.7% and 36.9% of the non-pregnant women, according to the Beck and HADS depression questionnaires, respectively, during the COVID-19 pandemic. The number of women who did not experience anxiety was the same in both groups, but non-pregnant women with anxiety had significantly higher scores on the HADS anxiety questionnaires. Additionally, pregnant women had significantly more negative dyadic adjustment in relationship quality than non-pregnant women. Relationship quality was a significant independent factor for BDI and both HADS depression and anxiety; pregnancy status was an important independent factor for depression (BDI and HADS depression); and work status was only a significant independent factor for BDI. Conclusion: This study highlights the significant impact of the COVID-19 pandemic on maternal mental health, with pregnant women experiencing elevated rates of depression compared to their non-pregnant counterparts. Future research should continue to explore the long-term consequences of maternal mental health challenges on maternal-infant outcomes and identify effective strategies for promoting maternal well-being in times of crisis.